2015
DOI: 10.1007/s11284-015-1260-8
|View full text |Cite
|
Sign up to set email alerts
|

The importance of residual habitats and crop management for the conservation of birds breeding in intensive orchards

Abstract: Intensive orchards are artificial habitats managed according to production criteria, but they may mimic open woodlands and harbour wild species. We investigated the effect of orchard features on the true abundance (estimated with occupancy models) of some bird species widespread in orchards. Our study was carried out in Val di Non (Trento province, Italy) where apple cultivation is the most widespread and intensive. We counted blackcaps Sylvia atricapilla, chaffinches Fringilla coelebs, and greenfinches Cardue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…Despite the fact that our landscape scale analysis relies on only 10 transects while groves were scarce in the matrix (0–11%), these woody structures positively influenced overall bird and thrush abundances, species richness and diversity especially during the winter season. The general preference for grove corroborates earlier findings in a variety of agroecosystems that hedges provide foraging, nesting and sheltering opportunities, as well as song posts for the avifauna [ 1 , 71 74 ]. The stronger positive effect of grove in winter might be related to the dominance of forest species which forage in open habitat but rely on woody patches offering sheltering opportunities.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Despite the fact that our landscape scale analysis relies on only 10 transects while groves were scarce in the matrix (0–11%), these woody structures positively influenced overall bird and thrush abundances, species richness and diversity especially during the winter season. The general preference for grove corroborates earlier findings in a variety of agroecosystems that hedges provide foraging, nesting and sheltering opportunities, as well as song posts for the avifauna [ 1 , 71 74 ]. The stronger positive effect of grove in winter might be related to the dominance of forest species which forage in open habitat but rely on woody patches offering sheltering opportunities.…”
Section: Discussionsupporting
confidence: 86%
“…While these results originate from only 10 transects and a single region in Switzerland, we are confident that the importance of natural structures and ground vegetation as well as the seasonal variability in habitat selection patterns can be generalized to at least vineyards from other regions [ 43 , 50 53 ] and potentially to other perennial crops such as orchards (e.g. [ 6 , 11 , 71 ]), if not even to other agroecosystems (e.g. [ 13 , 15 , 24 , 32 , 34 , 72 ]).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Results showed that meadow conversion caused a shift in the community composition towards assemblages dominated by generalist species, especially Turdidae and Fringilladae, which are known to adapt to intensive permanent monocultures (i.e. apple orchards and vineyards; Assandri et al., ; Brambilla, Assandri, Martino, Bogliani, & Pedrini, ), which usually replace semi‐natural grassland in the Alps. These changes occurred at the expense of the meadow specialists, which disappear with the increase in these crops.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the compatibility of bird conservation with agricultural land use is traditionally questioned (Balmford et al 2012), and birds constitute relevant bio-indicators of the environmental impact of agricultural practices (Furness and Greewood, 1983;Morelli et al 2014;Ormerod and Watkinson 2000). Therefore, identifying the drivers of bird species abundance in farmed landscapes is critical for assessing the bird population's response to human-driven changes in their habitats and counteracting adverse effects of agricultural practices on wildlife (Balmford et al 2012;Brambilla et al 2015).…”
Section: Introductionmentioning
confidence: 99%